Control algorithm for bidirectional fly-back active cell balancer with interleaved transformer connections - Saleh, Mojtaba; Masoum, Mohammad Sherkat; Meek, L.; Abshar, M. (2016)
Fly-back converter has proved a promising option for effective bidirectional active cell balancing in series connected battery stacks. The stack could be organized as a number of subsets to facilitate an interleaved connection across consecutive subsets at the high-voltage side of transformers so that the voltage rating of components will be reduced accordingly. This structure features expandable modular attribute, however, creates more complicated charge transfer between cells which has to be taken into account in the control scheme. This paper sets out the operation principals and proposes a control strategy handling intra-subset imbalance as well as inter-subset uneven charge distribution. The results of simulation study confirms the effectiveness of the proposed control method in both charge and discharge cycles.